Corrosion inhibition study of the protective reliability of Moringa oleifera, Chrysophyllum caimito, and Camellia sinensis oil distillates on mild steel in dilute H2SO4 and HCl solutions - Tolulope Loto Roland; Loto Cleophas; Oluseye Ayorinde (E3S Web of Conferences)
The protective reliability of Moringa oleifera (MO), Chrysophyllum caimito (CC), and Camellia sinensis (CS) oil distillates was examined in H2SO4 and HCl solutions. The data showed that MO and CC performed effectively in H2SO4 at 81.3% and 93% compared to CS at 76.5%. CC and CS performed more effectively in HCl at 92.7% and 93% compared to MO at 78.2%. The reliability output for CC in H2SO4, and CC and CS in HCl was generally constant. The lowest standard deviation values for H2SO4 were obtained for CC and CS, while the associated values for HCl were obtained for CS. At a accuracy range of +15, +9.1 and +20.2, the proportion of MO, CC and CS above 70% inhibition in H2SO4 is 71.4%, 95.2%, and 33.4% at accuracy range of +19.3, +0 and +0. The corresponding values from the HCl are 71.4%, 100% and 100% The results of the variance analysis show extract concentration and evaluation duration dominate the inhibition of MO and CS extracts in H2SO4, whereas in HCl they dominate the outputs for CC and CS. The inhibition of CC in H2SO4 are dominated by evaluation period, while the inhibition of MO in HCl is dominated by extract concentration.